International round robin test for tensile testing HTS wires at cryogenic temperatures. (16th January 2019) - Bagrets, N; Anvar, V A; Chiesa, L; Delgado, M A; McRae, D M; Nijhuis, A; Nishijima, G; Osamura, K; Shin, H S; Walsh, R P; Weiss, K-P; Zhang, Y; et al.
Abstract: Within the framework for establishing standards of test methods for superconducting technical wires, various standards have been issued by the International Electrotechnical Commission (IEC) (standard documents IEC 61788-1 to -20). Following the successful round robin test (RRT) for tensile testing REBCO wires at room temperature (Osamura K et al 2014 Supercond. Sci. Technol . 27 085009), this effort is extended to tensile test HTS wires at cryogenic temperatures and is coordinated by the CryoMaK lab at Karlsruhe Institute of Technology. Five different commercially available REBCO wires from five different manufacturers and one BiSCCO wire from another supplier were provided by the Versailles Project on Advanced Materials and Standards (http://vamas.org ) for testing. Samples were distributed between eight participating labs from five different countries for testing according to the specified guidelines. After the test results were delivered by all participants, the data were evaluated with statistical tools to investigate the main source of scatter and its magnitude in the test results. The final goal of the RRT is issuing an ISO/IEC standard for a cryogenic temperature tensile test for REBCO wires. In this report the results of the RRT for tensile testing REBCO wires at cryogenic temperatures are presented and discussed.